Potensi Quercetin sebagai Agen Antikanker pada Kanker Payudara: Tinjauan Literatur - Yekti Roro Hapsari (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Quercetin is a plant flavonol with antioxidant, anti-inflammatory, antiproliferative, and immunomodulatory properties that may be relevant to breast cancer therapy. This literature review aims to evaluate the potential of quercetin as an anticancer agent in breast cancer and to identify its main mechanisms, therapeutic combinations, and research gaps. Literature was reviewed from PubMed, ScienceDirect, Google Scholar, and open-access journal platforms using combinations of the keywords “quercetin,” “breast cancer,” “anticancer,” “apoptosis,” and “chemotherapy sensitization.” The review focused on articles published from 2021 to 2026 and included experimental, in vivo, organoid, and recent review studies directly related to quercetin and breast cancer. The synthesis shows that quercetin inhibits breast cancer cell growth through apoptosis induction, reactive oxygen species regulation, mitochondrial membrane disruption, caspase activation, cell-cycle arrest, senescence-related pathways, and suppression of epithelial-mesenchymal transition. Combination studies indicate synergistic or chemosensitizing effects. However, most evidence remains preclinical; clinical validation, pharmacokinetic studies, and delivery-system optimization are still required.